Utilização de resíduos de construção e demolição para pavimentos urbanos da região metropolitana de Fortaleza - Lima, João Henrique Camelo (2008)
The amount of construction waste from cities has been a concerning matter throughout the world due to the impact it has been causing to environmental, economic and social systems. Recycling is a sensible alternative and one of the most simple ways to use the recycled aggregate is in pavimentation. This study analyses laboratorialy the physical aspects and the mechanical behavior of recycled aggregate in the city of Fortaleza, to be used in base, sub-base or subleito enhancement layer, replacing the conventional materials, with focus on urban roads in Fortaleza metropolitan area (FMA). The study involved the characterization of construction and demolition waste (CDW) of mixed type in three forms (natural, with 2% of lime and with 2% of cement) and also of a conventional gravel from Itaitinga quarry - CE. Leaching and Solubilization tests were performed in RCD. Once familiar with the material (RCD and Brita), mechanical tests were performed (California Bearing /ratio, resistance to simple compression, resilient modulus and Tensile Strength) with recycled aggregate (natural and stabilized with lime and cement) and with gravel. Prime test was also performed on the mixtures with RCD. Finally, it was possible to compare technically and economically the aggregates studied. It was concluded that the recycled aggregate can be used in base and sub-base layers of pavements, and it was also economically competitive for use in the FMR.